2013
DOI: 10.1111/plb.12017
|View full text |Cite
|
Sign up to set email alerts
|

Differential response of antioxidative systems of maize (Zea mays L.) roots cell walls to osmotic and heavy metal stress

Abstract: An analysis of peroxidase and ascorbate oxidase activity, phenolic content and antioxidant capacity of isolated maize root cell walls was performed in controls and plants stressed with polyethylene glycol (PEG) or heavy metals, zinc or copper. Peroxidase activity (oxidative and peroxidative) was more pronounced in the ionic than in the covalent cell wall fraction. PEG induced an increase and Zn(2+) a decrease of both ionically bound peroxidase activities. In the covalent fraction, Cu(2+) decreased oxidative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 53 publications
1
12
0
Order By: Relevance
“…Alvarez et al (2008) analysed xylem sap of ʽFR697ʼ maize cultivar after 12 days of drought treatment and they observed the same pattern of hydroxycinnamic acids composition of the present study, reporting that t-ferulic acid was the predominant with a decreasing of 46% of this compound after drought treatment and this result was higher than the current experiment, in addition p-coumaric acid increased 286% which is a different behaviour comparing with the current results. Vuletić et al (2014), analysed the effect of osmotic stress in root cell walls of the maize inbred line ʽVA35ʼ and they found that content of total phenols diminished 30%, which is in agree with this results, but they also found a different behaviour in the analysis of hydroxycinnamic acids since they observed an increase of 49 and 18% in t-ferulic acid and p-coumaric respectively.…”
Section: Total Phenols and Hydroxycinnamic Acidssupporting
confidence: 73%
“…Alvarez et al (2008) analysed xylem sap of ʽFR697ʼ maize cultivar after 12 days of drought treatment and they observed the same pattern of hydroxycinnamic acids composition of the present study, reporting that t-ferulic acid was the predominant with a decreasing of 46% of this compound after drought treatment and this result was higher than the current experiment, in addition p-coumaric acid increased 286% which is a different behaviour comparing with the current results. Vuletić et al (2014), analysed the effect of osmotic stress in root cell walls of the maize inbred line ʽVA35ʼ and they found that content of total phenols diminished 30%, which is in agree with this results, but they also found a different behaviour in the analysis of hydroxycinnamic acids since they observed an increase of 49 and 18% in t-ferulic acid and p-coumaric respectively.…”
Section: Total Phenols and Hydroxycinnamic Acidssupporting
confidence: 73%
“…Moreover, ROS, such as H 2 O 2 and O2 are known secondary messages in several pathways associated with responses to biotic and abiotic stresses in plants (Apel and Hirt, 2004). Aside from their anti-oxidative activity, peroxidases are the most abundant enzymes in the cell wall where they display a multifunctional activity, also related to growth regulation (Vuletic et al, 2014). Peroxidases exist in multiple forms exhibiting different cellular localization and playing numerous biological functions.…”
Section: Resultsmentioning
confidence: 99%
“…The most abundant phenolic constituents of maize root cell walls are ferulic and p-coumaric acids (Vuletić et al, 2014) esterified with arabinoxylan (Hatfield et al, 1999) and lignin (Hatfield & Chaptman, 2009), respectively. Much greater increase in DPPH scavenging activity than in reducing power in the same cell wall isolates could be ascribed to the presence of ferulic acid esters, being extremely potent as DPPH radical scavengers and possessing weaker reducing power than free ferulic acid (Szwajgier et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In both cell wall fractions, mixed N induced the increase of MDH activities (>40%) in lateral roots only, while in primary roots the activity was decreased (Table 5). Ascorbate oxidase activity was found to be predominantly covalently bound (~ 95% of total activity) to the cell walls (Vuletić et al, 2014), and thus the effects of N forms were analyzed in NaCl-washed cell wall suspension. The activity was higher in nitrategrown plants (Table 6), in both lateral (27% increase) and primary roots (24% increase).…”
mentioning
confidence: 99%